The voices of Indigenous Peoples’ Elders in teacher training - Trapnell, Lucy (2017)
During the last decades the need to question the way in which knowledge is constructed as well as its relation with power issues has come forward. An important innovation in some teacher training colleges and conventional universities is the redefinition of the teaching staff. They have included indigenous elders as an attempt to open higher education to the inclusion of new actors and new voices. However, in this article I argue that the participation of indigenous elders in teacher training processes, does not necessarily guarantee the development of practises that will highlight the existence of ways of thinking alternative to hegemonic knowledge nor the multiple ways in which knowledge is produced. For this to happen consciousness must be gained regarding the complex relations between knowledge and power, and the way in which it is expressed in higher education in general and in specific academic spaces. Drawing from the experience of the Teacher Training Programme of the Peruvian Amazon (Formabiap), which I have accompanied during the last 29 years, I sustain my argument with information gained through my direct experience with the Programme and from documents, studies and internal and external evaluations of its process.